KAJIAN PENERAPAN GOOD MANUFACTURING PRACTICE (GMP) DI INDUSTRI RAJUNGAN PT.KELOLA MINA LAUT MADURA - Bhiaztika Ristyanadi; Darimiyya Hidayati (AGROINTEK, 2012)
Good manufacturing practice is the first step implementation of food safety regulation. PT. Kelola Mina Laut is one of chilled sea crab producers in Madura. It has four branches in Madura,those are in Tanjung Bumi, Noreh, Sampang, and Lobuk. The objective of this research is to assess the effectiveness GMP in four branches of PT. Kelola Mina Laut. The research  uses field observation, data analysis and GMP development as the method. Based on GMP analysis, four branches of PT. Kelola Mina Laut appear to have a cummulative score between 337-369, in which Lobuk has the highest score. Therefore, it can be concluded that PT. Kelola Mina Laut has applied most of GMP elements